La repercusión del entorno familiar saludable en la calidad del desempeño escolar en la escuela de educación básica juan benigno vela en el tercer año básico de la provincia de los ríos, cantón Ventanas, parroquia Zapotal - Molina Gutiérrez, Bélgica Irene (2016)
The lives of children and adolescents can be complex. Pressures imposed by the school, friends and parents can accumulate and create an environment of emotional stress, resulting in harmful eating habits that can continue into adulthood. The home is the most important site of our daily life, in which we share moments of rest, relaxation, work and coexistence, qualities that form a healthy family. It is therefore essential to keep it in optimum conditions, through good habits. The impact of a healthy family environment is fundamental for the development of society and for the formation of people with values, demonstrating respect for others and being aware of the opinions it imparts and the actions it performs. The family is the first school for children, where parents are an essential pillar for children to develop their skills and cognitive skills and to raise their quality of school performance, enabling them to make their own decisions. Institutions are then responsible for imparting knowledge to enable students to have meaningful learning and also to develop essential competencies so that they participate and act in solving problems of daily life.